PENGARUH MANAJEMEN LABA DAN EFISIENSI MANAJEMEN KAS TERHADAP PERFORMANCE PERUSAHAAN DENGAN MODERASI CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Non Keuangan yang terdaftar di BEI Tahun 2018-2022) - Vincentia Adhelia Putri Cantika; Imam Ghozali (Diponegoro Journal of Accounting, 2025)
This research explores how earnings management both accrual-based (AEM) and real-based (REM) along with cash management efficiency, influences a company’s financial performance. It also examines the moderating role of Corporate Social Responsibility (CSR) in these relationships. The study employs secondary data sourced from financial and sustainability reports of non-financial firms listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. The analysis was conducted using panel data regression with a fixed effects model. The results indicate that AEM positively contributes to financial performance, while REM exerts a negative impact. Efficient cash management also shows a influence on financial performance. Moreover, CSR is found to moderate these effects, strengthening beneficial relationships and buffering adverse ones. This study adds value to the existing literature by addressing CSR’s role in financial governance and offers practical insight for corporate stakeholders, including managers, regulators, and investors, to enhance sustainable financial performance.